Introduction of Artificial Intelligence to Students Using AIOT-kit Based on ThingSpeak - Trihandaru, Suryasatriya; Parhusip, Hanna Arini; Susanto, Bambang; Setiawan, Adi; Nugroho, Didit Budi; Kurniawan, Johanes Dian (Universitas Ahmad Dahlan, 2024)
Background: Schools struggle to engage students in science and technology, highlighting the need for innovative, tech-driven teaching methods to meet 21st-century educational demands. Contribution: An AIOT kit was developed to introduce middle school students to Artificial Intelligence (AI) and the Internet of Things (IoT). The kit measures environmental factors like temperature, humidity, pressure, and light, providing real-time data. Method: Students received training in mathematical and coding fundamentals, programmed the AIOT kit to collect data, and displayed it on the ThingSpeak dashboard. They also designed and assembled the kit, fostering peer-to-peer learning in future activities. Results: Students visualized data effectively and successfully connected the AIOT kit to the dashboard, confirming its functionality. Conclusion: The project enhanced students' understanding of AI and IoT, providing hands-on learning and boosting engagement in science and technology